Piezoelectric characteristics of urethane composites incorporating piezoelectric nanomaterials. (1st June 2020) - Kim, J.S.; Nam, I.W.; Lee, H.K.
Abstract: In the present study, piezoelectric energy generating composites were fabricated using three types of piezoelectric nanomaterials (lead zirconate titanate (PZT), zinc oxide, and barium titanate), along with two types of urethane matrices. The piezoelectric performance of the composites was evaluated in terms of the output voltage generated by external stamping loads. Based on the output voltage results, the effects of the type of piezoelectric nanomaterials, their content ratio, and the type of urethanes on the piezoelectric performance were systematically analyzed. The PZT nanomaterial-incorporated composites showed the best piezoelectric performance followed by ZnO nanomaterials- and BaTiO3 nanomaterials-incorporated composites. Vibrathane 6060-based composites were found to exhibit a greater output voltage than the Adiprene LF 900A-based composites due to their low hardness, bashore rebound, and compressive modulus. In addition, the effect of incorporating a multi-wall carbon nanotube (MWNT) on the piezoelectric performance was examined and the MWNT addition led to an adverse effect on piezoelectric performance due to the increase in the relative permittivity and the deterioration in the flexibility of the composites.